A variant RSA acceleration with parallelisation. Issue 3 (4th May 2022) - Liu, Jun-Jie; Tsang, Kang-Too; Deng, Yu-Hui
Abstract : The standard RSA relies on multiple big-number modular exponentiation operations and a longer key-length is required for better protection. This imposes a hefty time penalty for encryption and decryption. In this study, we analysed and developed an improved parallel algorithm (PMKRSA) based on the idea of splitting the plaintext into multiple chunks and encrypt the chunks using multiple key-pairs. The algorithm in our new scheme is so natural for parallelised implementation that we also investigated its parallelisation in a GPU environment. In the following, the structure of our new scheme is outlined and its correctness is proved mathematically. Then, with the algorithm implemented and optimised on both CPU and CPU+GPU platforms, we showed that our algorithm shortens the computational time considerably, and it has a security advantage over the standard RSA as it is invulnerable to the common attacks. Finally, we also proved the feasibility of using our algorithm to encrypt large files through simulation. The results show that over the set of file size: 1 MB, 10 MB, 25 MB, 50 MB, 100 MB, the average encryption and decryption time of the CPU version is 0.2476 and 9.4476 s, and for the CPU+GPU version, it is 0.0009 and 0.0618 s, respectively.